Analytical modelling of premises-specific solar energy estimation - K.A., K.A.; Khan, Sheroz; Yaacob,, Mashkuri; Khalifa, Othman Omran (2019)
Solar energy is great potential for future energy due affordability of solar related panels and equipment. SolarEnergy Microgrid for serving DC and AC loads of areas under consideration. Microgrid is a new concept for making safe, clean, and renewable solar available for use. Most of the countries have developed it solar farm in order to harvest the energy and make it useable for daily use. This energy can be used either for premises-specific loads and also distributed to other regions through the national grid through what is called Distributed Generation (DG). Estimating solar energy potential estimation of premises under target is obviously an exercise that may prove in the design of such DG microgrids. This paper presents two analytical modelling approaches for estimating the solar energy potential of a given geographical location. The two approaches are explored for estimation two very closely related amount of solar energy in kWh for eleven hours of time of a day using Heliocentris Hybrid Energy Lab-System data. The approaches may find utility in the pursuits of the renewable energy estimation needed for designing PV-solar microgrid. The mismatch of 6.31% energy estimation between the two approaches may be due to parametric complaint inaccuracy instead of the approaches employed